Principios y tecnologías linked data para la publicación de datos académicos de las diferentes carreras de la Universidad Nacional de Loja. - González Bustán, Ana María, Daniel Froilán Jiménez González (2016)
Considering, that today, there are several worldwide organizations which publish their data under the standards and principles of Linked Data, this Thesis Project (PFC for its acronym in Spanish), arises within the context of the Semantic Web and part of the importance of publishing information as a set of open and linked data. The PFC was carried out at the National University of Loja and aimed to provide a solution to its current web issues, semantically structuring the information relating to the academic offers of the University degrees. To achieve this goal, the following Semantic Web technologies were used: RDF, considered the standard language for publishing semantic data; and SPARQL, which is the language recommended by W3C for RDF data consultation. Some useful tools recommended by the Semantic Community were also used, for instance: Virtuoso Open Source, the tool in which RDF data was stored; and Pubby, through which the data visualization was made more user friendly. Additional tools that guaranteed a publication of good quality data were also indicated, these were: Open Refine, for data cleaning; Cmaps Tools for the conceptualization of information; and Protégé, for the creation of new vocabulary. In the development of the proposed topic, the process for the publication and generation of linked data was explained in detail, based largely on the study of concepts, tools and Linked Data projects and then by adopting a methodology of publication of linked data, the following activities were carried out: data selection and cleaning, vocabulary selection, creation of an ontology, generation and publication of RDF data.